Glomerular Hyper- and Hypofiltration During Acute Circulatory Failure: Iohexol-Based Gold-Standard Descriptive Study. Issue 8 (August 2019) - Salmon Gandonnière, Charlotte; Helms, Julie; Le Tilly, Olivier; Benz-de Bretagne, Isabelle; Bretagnol, Anne; Bodet-Contentin, Laetitia; Mercier, Emmanuelle; Halimi, Jean-Michel; Benzékri-Lefèvre, Dalila; Meziani, Ferhat; Barin-Le Guellec, Chantal; Ehrmann, Stephan
Abstract : Objective: To assess glomerular filtration rate in the early phase of acute circulatory failure by measuring iohexol plasma clearance. Design: Interventional prospective multicentric study. Setting: Three French ICUs in tertiary teaching hospitals. Patients: Patients with acute circulatory failure within 12 hours after ICU admission. Interventions: IV administration of a nontoxic 5-mL dose of iohexol. Collection of nine arterial blood samples over 24 hours for iohexol plasma concentration measurements. Iohexol clearance calculation with a population pharmacokinetic model. Iohexol clearance was an estimation of the mean glomerular filtration rate over 24 hours. Measurements and Main Results: Among 99 included patients, we could calculate iohexol clearance for 85. The median iohexol clearance was 31 mL/min (interquartile range, 16–44). According to iohexol clearance, 41 patients (48%) had severe hypofiltration (clearance, < 30 mL/min), 29 (34%) had moderate hypofiltration, and 10 (12%) had mild hypofiltration (clearance, 30–60 and 60–90 mL/min, respectively). Four patients (5%) had normal glomerular filtration rate, and only one (1%) showed hyperfiltration (clearance, > 130 mL/min). Urinary creatinine clearance underestimated renal impairment in one patient out of two; the bias of iohexol clearance toward 24-hour urinary creatinine clearance over the same period was –18.1 mL/min (limits of agreement, –73.5 to 37.4). Conclusions: We demonstrated the feasibility of iohexol clearance measurement in unstable critically ill patients. Normal kidney function is exceptional during the early phase of acute circulatory failure. Glomerular filtration rate estimation by urinary creatinine clearance frequently fails to detect renal impairment. Hyperfiltration is very infrequent. Abstract : Supplemental Digital Content is available in the text.